2018
DOI: 10.1088/2053-1583/aab80e
|View full text |Cite
|
Sign up to set email alerts
|

Impurity-assisted electric control of spin-valley qubits in monolayer MoS 2

Abstract: We theoretically study a single-electron spin-valley qubit in an electrostatically defined quantum dot in a transition metal dichalcogenide monolayer, focusing on the example of MoS2. Coupling of the qubit basis states for coherent control is challenging, as it requires a simultaneous flip of spin and valley. Here, we show that a tilted magnetic field together with a short-range impurity, such as a vacancy, a substitutional defect, or an adatom, can give rise to a coupling between the qubit basis states. This … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 52 publications
0
52
0
Order By: Relevance
“…A recipe for a CNOT gate with these states is readily available from the original Loss and DiVincenzo proposal for spin-only qubits [46]. If, in addition, the τ x operation could be effectively implemented (theoretical proposals to achieve this include the use of impurities [35,61] or the use of oscillating confinement potentials [36]), then we would also have a full set for single qubit operations. Moving to the asymmetric spin-orbit splitting we found that only the exchange energy is affected, while the form of the exchange Hamiltonian remains unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…A recipe for a CNOT gate with these states is readily available from the original Loss and DiVincenzo proposal for spin-only qubits [46]. If, in addition, the τ x operation could be effectively implemented (theoretical proposals to achieve this include the use of impurities [35,61] or the use of oscillating confinement potentials [36]), then we would also have a full set for single qubit operations. Moving to the asymmetric spin-orbit splitting we found that only the exchange energy is affected, while the form of the exchange Hamiltonian remains unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…The monolayer is then covered with a 5 nm thick insulating layer of hexagonal boron nitride (hBN) with a large bandgap [32], forming a tunnel barrier. Finally on top of the sandwiched structure we lay down four 15 nm wide control gates (G 1.. 4 ), placed symmetrically around the central square-like gap of size 20×20 nm. The gate layout presented here is quite similar to the one proposed by us recently [3], but with a larger 20 nm clearance between opposite gates, which may ease their deposition.…”
Section: Device Structurementioning
confidence: 99%
“…Voltages applied to these gates (relative to the substrate) are used to create confinement in the flake. To calculate realistic electrostatic potential f(r) we solve the Poisson equation taking into account voltages V 1..4 applied to control gates G 1.. 4 and to the highly doped substrate V 0 = 0, together with space-dependent permittivity of different materials in the device [3,33]. Resulting potential in the area between SiO 2 and hBN layers, where the flake is sandwiched, is presented in figure 2.…”
Section: Device Structurementioning
confidence: 99%
See 1 more Smart Citation
“…EDSR requires the coupling of the qubit spin states to an external AC-electric field 47,48 , which drives rotations between the spin states, such that ideally microwave pulses can be used to perform the desired single qubit gate. This has been theoretically shown to be achievable in TMD QDs adopting a Kramers qubit architechure, with the aid of an additional lattice defect to mix the valley states 40 . We show that in a valley-polarised pure-spin qubit architechure, EDSR is achievable and with some parameter optimisation (dot radius, magnetic fields etc.)…”
Section: Introductionmentioning
confidence: 99%